The Impact of Biogas Adoption on Household Food Security among Livestock Farmers - Nugroho, Taufik Rizal Dwi Adi; Firdaus, Mohammad Wahyu; Hayati, Mardiyah (Universitas Djuanda, 2025)
Biogas technology has emerged as a strategic solution to address energy and environmental challenges in rural agricultural communities. However, its adoption rate and impact on household welfare—particularly regarding food security—remain relatively underexplored within the local Indonesian context. This study aims to: (1) identify the socio-economic and demographic factors influencing household decisions to adopt biogas technology, and (2) evaluate the impact of biogas adoption on household food security. The research was conducted using a cross-sectional survey design in Gendro Village, Tutur Subdistrict, Pasuruan Regency, Indonesia. A total of 129 livestock-farming households were purposively selected. Data were collected through structured questionnaires and analyzed using probit regression and two-sample t-tests. The findings indicate that farming experience (p = 0.051), livestock ownership (p = 0.054), membership in farmer groups (p = 0.025), and participation in extension programs (p = 0.070) significantly influence biogas adoption decisions. Furthermore, the t-test results show a statistically significant difference in food security between adopter and non-adopter households (p = 0.000). This study represents one of the first quantitative efforts in Indonesia to empirically examine the relationship between biogas technology adoption and household food security using the Food Insecurity Experience Scale (FIES). The results affirm that biogas technology contributes to energy savings and waste management and positively affects food security outcomes. Therefore, policy interventions should focus on expanding access to biogas technology through subsidy schemes, technical training, and integration with sustainable livestock development programs. Moreover, strengthening farmer group empowerment and community-based approaches is essential to promote wider and more equitable technology dissemination.